La ciudadanía como construcción histórico-social y sus transformaciones en la Argentina contemporánea - Perissé, Agustín Horacio (Nómadas. Critical Journal of Social and Juridical Science, 2010)
In this work one raises that it she brings the conceptions over of the citizenship they are transforming throughout the time and in the different social formations. To support this one I raise there is realized a historical tour been founded on the experts’ expositions of the topic brings over of the meanings that the citizenship has assumed in different societies as the ancient Greece, Rome and the national European States of the 19th century. Then there is planned the influence that the conceptions exercised of the above mentioned in the emergence of the Argentine State, and in the configuration of the citizenship in our country. Distinguish themselves the transformations that have suffered the conceptions it she brings over of the citizenship in the Argentina of last thirty years, as result of the changes that took place were produced in the relations between State, society and market. Finally there is supported the need of his your investigation, and there are formulated some conclusions referred to the need to clarify the senses of the citizenship proposed by the political and social actors of the Argentine society.